Effect of nano α-MnO2 addition on thermal decomposition and compressive properties of epoxy - Hussain, Md Zakir; Sarmah, Pranjal (International Journal of Integrated Engineering, 2024)
The ability of a nanocomposite material to withstand high temperatures and maintain strength is crucial for the design of products and processes. This research examined the thermal decomposition and compressive properties of α-MnO2/epoxy polymer nanocomposites. The samples were created using a simple, inexpensive solution technique. The scanning electron microscope, X-ray diffraction, and energy-dispersive X-ray analysis indicated the formation of α-MnO2 nanosheets. The thermal analysis revealed that the addition of α-MnO2 increased the glass transition temperature of the epoxy. Thermogravimetric analysis showed that the residue was left at 550°C for a sample of pure epoxy with a loading of 0.1 wt.%. 0.2 wt.%, 0.3 wt.%, and 0.5 wt.% of α-MnO2 were 9.55%, 11.05%, 16.78%, 17.37%, and 21.20%, respectively. As a result, the nanocomposites were more thermally stable than pure epoxy. The compressive characteristics were tested using a universal testing machine. Compression test results showed that the addition of α-MnO2 decreased the compressive properties of the epoxy matrix. However, the brittleness of nanocomposites increased. Images captured at the microscopic level showed that the sample cracked and fractured during testing. The reduced compressive property values were associated with reduced α-MnO2 dispersion in the epoxy, the shape of α-MnO2 nanosheets, and the generation of air voids during the synthesis process. As a result, the α-MnO2 nanosheets reduce the compressive properties of the nanocomposites by acting as stress enhancers. The nanocomposite can be used as a thermal heat-resistant material.